(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study is anchored on socio-economic tourism and its implication for national development plan in Cross River State experience. This paper was stratified into three cities within the state. Four hundred questionnaires were at administered to citizens within the three cities, while interview were conducted among some selected staff of the state tourism commission. One hypothesis was formulated and tested using person moment correlation. The paper indicates that, several prospect occur to socio-economic tourism and its national development plan in the study area. It was observed that poor planning constitute a major challenges to socio-economic tourism plan in the study area as showed from the hypothesis which indicate positive significant relationship between the challenge and prospect of socio-economic tourism and national development plain in the study area. It is on this note that, the government and non-governmental organization must ensure that the challenge of socio-economic tourism and national development plan are adverted through proper monitory, proper distribution of resources, employment opportunity, training and retraining of staff to promote effective development tourism site in Cross River State.